An Assessment of COVID-19 Mortality Risk with A Novel Scoring Method in A Tertiary Care Hospital in Andhra Pradesh: A Prospective Study - V. Sathish Kumar; N. Venkata Shanmukharao; M. Saianjani Reddy; M. Amar Teja; T. Uma Shankar (International Journal of Pharma and Bio Sciences, 2023)
Coronavirus (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). COVID- 19 affected people clinically present with symptoms of fever, fatigue, loss of appetite, cough with sputum production, anosmia, nausea, vomiting, gastroenteritis, and shortness of breath. During covid pandemic, to assess the severity, we developed a novel scoring system, i.e., ACHE. The increasing score suggests an increase in severity and a possible increased mortality rate. Different parameters were included in developing a scoring system to evaluate the patient's severity. A Prospective observational study on the Covid-19 mortality risk assessment with a novel evaluation scoring in a tertiary care hospital in Andhra Pradesh. The objective is to predict the mortality risk of COVID-19 patients at admission by a novel scoring system, i.e., ACHE score (Acute covid health evaluation), and to categorize the patient using a novel acute covid health evaluation (ACHE) score—a hospital-based prospective observational study which included 800 cases of covid 19 confirmed by RT – PCR. ACHE was calculated in all these patients based on 4 major parameters: NL neutrophil-lymphocyte ratio (NLR) ratio, CRP(C-REACTVE PROTEIN), D – Dimer &Age group. Different parameters were included in developing the scoring system to evaluate the patient's severity. The novel scoring system ACHE scores>15 had the highest mortality rate. And Majority of the patients out of 800 were in the age group 51-60 (n=208, 26%) and had shown more prevalence, followed by the age group 61-70 (n=178, 22.25%). Among 800 patients, 87 died due to viral pneumonia with cytokine storm, coagulopathy, sepsis, and MODS. In the background of covid pandemic, a simplified way of assessing the severity of covid patients is the need of the hour. ACHE scoring system helped assess the patient's condition and prognosis, thus aiding in making a dynamic decision in managing the patients without any undue delay to reduce morbidity and mortality.